Influence of External Pressures of Different Symmetry on the Phase Transitions and Thermodynamic of the RbHSO4 Ferroelectrics - Zachek, I.R.; Karkuljevska, M.C.; Vdovych, A.S.; Levitsky, R.R. (Physics and Chemistry of Solid State, 2015)
We use the four-sublattice model of the RbHSO4 crystal modified by taking into account the piezoelectric coupling to the strains , . Within the mean field approximation we calculate the components of the polarization vector and static dielectric permittivity tensor of mechanically clamped and free crystals, as well as their piezoelectric characteristics. We study the influence of hydrostatic pressure and uniaxial stresses on the phase transition and physical characteristics of the crystal. A good quantitative description of the experimental data is obtained.